Can we reduce oxidative stress with liver transplantation? oxidative stress in cirrhosis and after transplantation - Aydin, Mesut (Journal of Medical Biochemistry, 2021)
Background: The aim of this study was to determine the levels of lipid peroxidation (MDA) and antioxidants such as reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) in the blood serum of patients with cirrhosis and liver transplantation. Materials and Methods: In this study, serum malondialdehyde acid (MDA) levels, superoxide dismutase (SOD), reduced glutathione (GSH), and catalase (CAT) activities were measured spectrophotometrically and compared to the results of the healthy control group. Results: SOD, CAT and GSH activities were significantly decreased in the patient groups compared to the healthy control group (p<0.05). MDA levels were significantly higher in the patient group compared to the healthy control group (p <0.05). Conclusion: In conclusion, this study demonstrated that oxidative stress may play an important role in the development of liver cirrhosis and in liver transplantation. This study is the first one to show how MDA, SOD, CAT and GSH levels change in liver cirrhosis and liver transplantation, while further studies are essential to investigate antioxidant enzymes and oxidative stress status in patients with cirrhosis and liver transplantation.